mTOR Blockade by Rapamycin in Spondyloarthritis: Impact on Inflammation and New Bone Formation in vitro and in vivo - Chen, Sijia; van Tok, Melissa N.; Knaup, Véronique L.; Kraal, Lianne; Pots, Désiree; Bartels, Lina; Gravallese, Ellen M.; Taurog, Joel D.; van de Sande, Marleen; van Duivenvoorde, Leonie M.; Baeten, Dominique L. (Frontiers in Immunology, 2020)
Introduction: Spondyloarthritis (SpA) is characterized by inflammation, articular bone erosions and pathologic new bone formation. Targeting TNFα or IL-17A with current available therapies reduces inflammation in SpA, however, treatment of the bone pathology in SpA remains an unmet clinical need. Activation of the mammalian target Of rapamycin (mTOR) promotes IL-17A expression and osteogenesis. Therefore, the inhibition of mTOR (with rapamycin) could be a promising therapeutic avenue in SpA. Objectives: To investigate the effect of blocking mTOR on inflammation, bone erosions and new bone formation in SpA. Methods: Peripheral blood mononuclear cells (PBMCs) from patients with SpA were stimulated with anti-CD3/CD28 in the presence or absence of rapamycin and the resulting cytokine expression was assessed. Fibroblast-like synoviocytes (FLS) from SpA patients were assessed for osteogenic differentiation potential in conditions with TNFα, IL-17A, or TNFα plus IL-17A, in the presence or absence of rapamycin. HLA-B27/Huβ2m transgenic rats were immunized with low dose heat-inactivated Mycobacterium tuberculosis (M. tub), treated with 1.5 mg/kg rapamycin prophylactically or therapeutically and monitored for arthritis and spondylitis. Histology and mRNA analysis were performed after 5 weeks of treatment to assess inflammation and bone pathology. Results:In vitro TNFα and IL-17A protein production by SpA PBMCs was inhibited in the presence of rapamycin. Rapamycin also inhibited osteogenic differentiation of human SpA FLS. Ex vivo analysis of SpA synovial biopsies indicated activation of the mTOR pathway in the synovial tissue of SpA patients. In vivo, prophylactic treatment of HLA-B27/Huβ2m transgenic rats with rapamycin significantly inhibited the development and severity of inflammation in peripheral joints and spine (arthritis and spondylitis), with histological evidence of reduced bone erosions and new bone formation around peripheral joints. In addition, therapeutic treatment with rapamycin significantly decreased severity of arthritis and spondylitis, with peripheral joint histology showing reduced inflammation, bone erosions and new bone formation. IL-17A mRNA expression was decreased in the metacarpophalangeal joints after rapamycin treatment. Conclusion: mTOR blockade inhibits IL-17A and TNFα production by PBMCs, and osteogenic differentiation of FLS from patients with SpA in vitro. In the HLA-B27 transgenic rat model of SpA, rapamycin inhibits arthritis and spondylitis development and severity, reduces articular bone erosions, decreases pathologic new bone formation and suppresses IL-17A expression. These results may support efforts to evaluate the efficacy of targeting the mTOR pathway in SpA patients.